Integration Questions

Question Number 126203 by frc2crc last updated on 18/Dec/20

$$\overset{\infty} {\int}_{\mathrm{0}} \frac{\mathrm{1}}{\mathrm{1}+{x}^{{s}} +{x}^{\mathrm{2}{s}} } \\$$

Answered by Olaf last updated on 18/Dec/20

$$\\$$$$\mathrm{1}+{x}^{{s}} +{x}^{\mathrm{2}{s}} \:=\:\mathrm{0} \\$$$$\left({x}^{{s}} −{e}^{{i}\frac{\mathrm{2}\pi}{\mathrm{3}}} \right)\left({x}^{{s}} −{e}^{−{i}\frac{\mathrm{2}\pi}{\mathrm{3}}} \right)\:=\:\mathrm{0} \\$$$${x}\:=\:{e}^{{i}\left(\frac{\mathrm{2}\pi}{\mathrm{3}{s}}+\frac{\mathrm{2}{k}\pi}{{s}}\right)} \:\mathrm{or}\:{x}\:=\:{e}^{{i}\left(−\frac{\mathrm{2}\pi}{\mathrm{3}{s}}+\frac{\mathrm{2}{k}\pi}{{s}}\right)} ,\:{k}\:=\:\mathrm{0}...{s}−\mathrm{1} \\$$$${x}\:=\:{e}^{{i}\frac{\mathrm{2}\pi}{{s}}\left(\mathrm{2}{k}+\frac{\mathrm{1}}{\mathrm{3}}\right)} \:\mathrm{or}\:{x}\:=\:{e}^{{i}\frac{\mathrm{2}\pi}{{s}}\left(\mathrm{2}{k}−\frac{\mathrm{1}}{\mathrm{3}}\right)} ,\:{k}\:=\:\mathrm{0}...{s}−\mathrm{1} \\$$$$\mathrm{Let}\:{x}_{{k}} ^{\oplus} \:=\:{e}^{{i}\frac{\mathrm{2}\pi}{{s}}\left(\mathrm{2}{k}+\frac{\mathrm{1}}{\mathrm{3}}\right)} \:\mathrm{and}\:{x}_{{k}} ^{\circleddash} \:=\:{e}^{{i}\frac{\mathrm{2}\pi}{{s}}\left(\mathrm{2}{k}−\frac{\mathrm{1}}{\mathrm{3}}\right)} \\$$$$\mathrm{R}\left({x}\right)\:=\:\frac{\mathrm{1}}{\mathrm{1}+{x}^{{s}} +{x}^{\mathrm{2}{s}} } \\$$$$\mathrm{R}\left({x}\right)\:=\:\frac{\mathrm{1}}{\underset{{k}=\mathrm{0}} {\overset{{s}−\mathrm{1}} {\prod}}\left({x}−{x}_{{k}} ^{\oplus} \right)×\underset{{k}=\mathrm{0}} {\overset{{s}−\mathrm{1}} {\prod}}\left({x}−{x}_{{k}} ^{\circleddash} \right)} \\$$$$\mathrm{R}\left({x}\right)\:=\:\underset{{p}=\mathrm{0}} {\overset{{s}−\mathrm{1}} {\sum}}\frac{\mathrm{A}_{{p}} ^{\oplus} }{{x}−{x}_{{p}} ^{\oplus} }+\underset{{p}=\mathrm{0}} {\overset{{s}−\mathrm{1}} {\sum}}\frac{\mathrm{A}_{{p}} ^{\circleddash} }{{x}−{x}_{{p}} ^{\circleddash} } \\$$$$\mathrm{A}_{{p}} ^{\oplus} \:=\:\frac{\mathrm{1}}{\underset{\underset{{k}\neq{p}} {{k}=\mathrm{0}}} {\overset{{s}−\mathrm{1}} {\prod}}\left({x}_{{p}} ^{\oplus} −{x}_{{k}} ^{\oplus} \right)×\underset{{k}=\mathrm{0}} {\overset{{s}−\mathrm{1}} {\prod}}\left({x}_{{p}} ^{\oplus} −{x}_{{k}} ^{\circleddash} \right)} \\$$$$\mathrm{A}_{{p}} ^{\circleddash} \:=\:\frac{\mathrm{1}}{\underset{{k}=\mathrm{0}} {\overset{{s}−\mathrm{1}} {\prod}}\left({x}_{{p}} ^{\circleddash} −{x}_{{k}} ^{\oplus} \right)×\underset{\underset{{k}\neq{p}} {{k}=\mathrm{0}}} {\overset{{s}−\mathrm{1}} {\prod}}\left({x}_{{p}} ^{\circleddash} −{x}_{{k}} ^{\circleddash} \right)} \\$$$$\mathrm{I}\:=\:\int_{\mathrm{0}} ^{\infty} \mathrm{R}\left({x}\right){dx} \\$$$$\mathrm{I}\:=\:\underset{{p}=\mathrm{0}} {\overset{{s}−\mathrm{1}} {\sum}}\int_{\mathrm{0}} ^{\infty} \left[\frac{\mathrm{A}_{{p}} ^{\oplus} }{{x}−{x}_{{p}} ^{\oplus} }+\frac{\mathrm{A}_{{p}} ^{\circleddash} }{{x}−{x}_{{p}} ^{\circleddash} }\right]{dx} \\$$$$\mathrm{I}\:=\:\underset{{p}=\mathrm{0}} {\overset{{s}−\mathrm{1}} {\sum}}\left[\mathrm{A}_{{p}} ^{\oplus} \mathrm{ln}\mid{x}−{x}_{{p}} ^{\oplus} \mid+\mathrm{A}_{{p}} ^{\circleddash} \mathrm{ln}\mid{x}−{x}_{{p}} ^{\circleddash} \mid\right]_{\mathrm{0}} ^{\infty} \\$$$$...\mathrm{to}\:\mathrm{be}\:\mathrm{continued}... \\$$$$\mathrm{I}'\mathrm{m}\:\mathrm{not}\:\mathrm{sure}\:\mathrm{it}'\mathrm{s}\:\mathrm{a}\:\mathrm{good}\:\mathrm{way}... \\$$

Answered by Dwaipayan Shikari last updated on 18/Dec/20

$$\int_{\mathrm{0}} ^{\infty} \frac{\mathrm{1}}{\mathrm{1}+{x}^{{s}} +{x}^{\mathrm{2}{s}} }{dx}\:\:\:\:\:\:\:\:\:{x}^{{s}} ={t}\: \\$$$$=\frac{\mathrm{1}}{{s}}\int_{\mathrm{0}} ^{\infty} {t}^{\frac{\mathrm{1}−{s}}{{s}}} \frac{\mathrm{1}}{\mathrm{1}+{t}+{t}^{\mathrm{2}} }{dt}\:=\frac{\mathrm{1}}{{s}}\int_{\mathrm{0}} ^{\infty} {t}^{\frac{\mathrm{1}−{s}}{{s}}} .\frac{\mathrm{1}}{\left({t}−{e}^{\frac{\mathrm{2}{i}\pi}{\mathrm{3}}} \right)\left({t}−{e}^{−\frac{\mathrm{2}\pi{i}}{\mathrm{3}}} \right)}{dt} \\$$$$=\frac{\mathrm{1}}{{s}\left({e}^{\frac{\mathrm{2}{i}\pi}{\mathrm{3}}} −{e}^{−\frac{\mathrm{2}{i}\pi}{\mathrm{3}}} \right)}\int_{\mathrm{0}} ^{\infty} \frac{{t}^{{a}} }{{t}−{e}^{\frac{\mathrm{2}{i}\pi}{\mathrm{3}}} }−\frac{\mathrm{1}}{{s}\left({e}^{\frac{\mathrm{2}{i}\pi}{\mathrm{3}}} −{e}^{\frac{−\mathrm{2}{i}\pi}{\mathrm{3}}} \right)}\int_{\mathrm{0}} ^{\infty} \frac{{t}^{{a}} }{{t}−{e}^{−\frac{\mathrm{2}{i}\pi}{\mathrm{3}}} } \\$$$$=\frac{\mathrm{1}}{\Lambda}\int_{\mathrm{0}} ^{\infty} \frac{{t}^{{a}} }{{t}+{m}}−\frac{{t}^{{a}} }{{t}+{b}}{dt}\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:{t}={my}\Rightarrow\mathrm{1}={m}\frac{{dy}}{{dt}}\:\:\:\:{t}={bj}\Rightarrow\mathrm{1}={b}\frac{{dj}}{{dt}} \\$$$$=\frac{{m}^{{a}} }{\Lambda}\int_{\mathrm{0}} ^{\infty} \frac{{y}^{{a}} }{{y}+\mathrm{1}}−\frac{{b}^{{a}} }{\Lambda}\int\frac{{j}^{{a}} }{{j}+\mathrm{1}}{dj} \\$$$$\int_{\mathrm{0}} ^{\infty} \frac{{y}^{{a}} }{{y}+\mathrm{1}}{dy}\:\:\:\:\:\:\:\:\:\:\:\:\frac{{y}}{{y}+\mathrm{1}}={g}\Rightarrow\frac{\mathrm{1}}{\left(\mathrm{1}+{y}\right)^{\mathrm{2}} }=\frac{{dg}}{{dy}} \\$$$$=\int_{\mathrm{0}} ^{\mathrm{1}} {y}^{{a}−\mathrm{1}} \frac{{g}}{\left(\mathrm{1}−{g}\right)^{\mathrm{2}} }{dg}\:\:\:\:\:\:=\int_{\mathrm{0}} ^{\mathrm{1}} {g}^{{a}} \left(\mathrm{1}−{g}\right)^{−{a}−\mathrm{1}} {dg}=−\pi{cosec}\left(\pi{a}\right) \\$$$${Similarly}\:\int_{\mathrm{0}} ^{\infty} \frac{{j}^{{a}} }{{j}+\mathrm{1}}=−\pi{cosec}\left(\pi{a}\right) \\$$$${I}=−\frac{\pi{cosec}\:\pi{a}}{\Lambda}\left({m}^{{a}} −{b}^{{a}} \right)\:\left({a}=\frac{\mathrm{1}−{s}}{{s}}\:,\:\Lambda=\mathrm{2}{issin}\frac{\mathrm{2}\pi}{\mathrm{3}},{m}=−{e}^{\frac{\mathrm{2}\pi{i}}{\mathrm{3}}} {b}=−{e}^{\frac{−\mathrm{2}\pi{i}}{\mathrm{3}}} \right) \\$$$${Not}\:{sure}\:{if}\:{it}\:{is}\:{true}\:{or}\:{not}... \\$$

Answered by mathmax by abdo last updated on 19/Dec/20

$$\mathrm{A}_{\mathrm{s}} =\int_{\mathrm{0}} ^{\infty} \:\:\frac{\mathrm{dx}}{\mathrm{1}+\mathrm{x}^{\mathrm{s}} \:+\mathrm{x}^{\mathrm{2s}} }\:\:\mathrm{we}\:\mathrm{do}\:\mathrm{the}\:\mathrm{changement}\:\mathrm{x}^{\mathrm{s}} \:=\mathrm{t}\:\Rightarrow\mathrm{x}=\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{s}}} \left(\mathrm{we}\:\mathrm{suppise}\:\mathrm{s}\:\mathrm{real}\right) \\$$$$\Rightarrow\:\mathrm{A}_{\mathrm{s}} =\frac{\mathrm{1}}{\mathrm{s}}\int_{\mathrm{0}} ^{\infty} \:\:\:\frac{\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} }{\mathrm{t}^{\mathrm{2}} \:+\mathrm{t}+\mathrm{1}}\mathrm{dt}\:\:\:\mathrm{roots}\:\mathrm{of}\:\mathrm{t}^{\mathrm{2}} \:+\mathrm{t}+\mathrm{1}=\mathrm{0}\:\rightarrow\Delta=−\mathrm{3}\:\Rightarrow \\$$$$\mathrm{t}_{\mathrm{1}} =\frac{−\mathrm{1}+\mathrm{i}\sqrt{\mathrm{3}}}{\mathrm{2}}=\mathrm{e}^{\frac{\mathrm{i2}\pi}{\mathrm{3}}} \:\:\mathrm{and}\:\mathrm{t}_{\mathrm{2}} =\frac{−\mathrm{1}−\mathrm{i}\sqrt{\mathrm{3}}}{\mathrm{2}}=\mathrm{e}^{−\frac{\mathrm{i2}\pi}{\mathrm{3}}} \:\Rightarrow \\$$$$\mathrm{A}_{\mathrm{s}} =\frac{\mathrm{1}}{\mathrm{s}}\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} }{\left(\mathrm{t}−\mathrm{e}^{\frac{\mathrm{i2}\pi}{\mathrm{3}}} \right)\left(\mathrm{t}−\mathrm{e}^{−\frac{\mathrm{i2}\pi}{\mathrm{3}}} \right)}\mathrm{dt}\:=\frac{\mathrm{1}}{\mathrm{s}}\int_{\mathrm{0}} ^{\infty} \left(\frac{\mathrm{1}}{\mathrm{t}−\mathrm{e}^{\frac{\mathrm{i2}\pi}{\mathrm{3}}} }−\frac{\mathrm{1}}{\mathrm{t}−\mathrm{e}^{−\frac{\mathrm{i2}\pi}{\mathrm{3}}} }\right)\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} \:\mathrm{dt} \\$$

Commented by mathmax by abdo last updated on 19/Dec/20

$$\mathrm{A}_{\mathrm{s}} =\frac{\mathrm{1}}{\mathrm{s}\left(\mathrm{2isin}\left(\frac{\pi}{\mathrm{3}}\right)\right)}\left\{\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} }{\mathrm{t}−\mathrm{e}^{\frac{\mathrm{i2}\pi}{\mathrm{3}}} }\mathrm{dt}−\int_{\mathrm{0}} ^{\infty} \:\:\frac{\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} }{\mathrm{t}−\mathrm{e}^{−\frac{\mathrm{i2}\pi}{\mathrm{3}}} }\mathrm{dt}\right\} \\$$$$\mathrm{A}_{\mathrm{s}} =\frac{\mathrm{1}}{\mathrm{is}\sqrt{\mathrm{3}}}\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} }{\mathrm{t}+\mathrm{e}^{\mathrm{i}\left(\pi+\frac{\mathrm{2}\pi}{\mathrm{3}}\right)} }\mathrm{dt}−\frac{\mathrm{1}}{\mathrm{is}}\int_{\mathrm{0}} ^{\infty} \:\:\frac{\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} }{\mathrm{t}+\mathrm{e}^{\mathrm{i}\left(\pi−\frac{\mathrm{2}\pi}{\mathrm{3}}\right)} }\mathrm{dt}\:\:\mathrm{we}\:\mathrm{have} \\$$$$\int_{\mathrm{0}} ^{\infty} \:\:\frac{\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} }{\mathrm{t}+\mathrm{e}^{\mathrm{i}\left(\frac{\mathrm{5}\pi}{\mathrm{3}}\right)} }\mathrm{dt}\:=_{\mathrm{t}\:=\mathrm{e}^{\mathrm{i}\frac{\mathrm{5}\pi}{\mathrm{3}}} \mathrm{z}} \:\:\int_{\mathrm{0}} ^{\infty} \:\frac{\left(\mathrm{e}^{\frac{\mathrm{i5}\pi}{\mathrm{3}}} \right)^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} \mathrm{z}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} }{\mathrm{e}^{\frac{\mathrm{i5}\pi}{\mathrm{3}}} \left(\mathrm{1}+\mathrm{z}\right)}\mathrm{e}^{\frac{\mathrm{i5}\pi}{\mathrm{3}}} \:\mathrm{dz} \\$$$$=\:\mathrm{e}^{\frac{\mathrm{5i}\pi}{\mathrm{3}}\left(\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}\right)} \:\:\:×\frac{\pi}{\mathrm{sin}\left(\frac{\pi}{\mathrm{s}}\right)}\:\mathrm{also} \\$$$$\int_{\mathrm{0}} ^{\infty} \:\:\:\frac{\mathrm{t}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} }{\mathrm{t}+\mathrm{e}^{\frac{\mathrm{i}\pi}{\mathrm{3}}} }\mathrm{dt}\:=_{\mathrm{t}=\mathrm{e}^{\frac{\mathrm{i}\pi}{\mathrm{3}}} \mathrm{z}} \:\:\int_{\mathrm{0}} ^{\infty} \:\:\frac{\left(\mathrm{e}^{\frac{\mathrm{i}\pi}{\mathrm{3}}} \right)^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} \mathrm{z}^{\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}} }{\mathrm{e}^{\frac{\mathrm{i}\pi}{\mathrm{3}}} \left(\mathrm{1}+\mathrm{z}\right)}\mathrm{e}^{\frac{\mathrm{i}\pi}{\mathrm{3}}} \mathrm{dz} \\$$$$=\mathrm{e}^{\frac{\mathrm{i}\pi}{\mathrm{3}}\left(\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}\right)} ×\frac{\pi}{\mathrm{sin}\left(\frac{\pi}{\mathrm{s}}\right)}\:\Rightarrow \\$$$$\mathrm{A}_{\mathrm{s}} =\frac{\mathrm{1}}{\mathrm{is}\sqrt{\mathrm{3}}}×\frac{\pi}{\mathrm{sin}\left(\frac{\pi}{\mathrm{s}}\right)}\left(\:\mathrm{e}^{\frac{\mathrm{5i}\pi}{\mathrm{3}}\left(\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}\right)} −\mathrm{e}^{\frac{\mathrm{i}\pi}{\mathrm{3}}\left(\frac{\mathrm{1}}{\mathrm{s}}−\mathrm{1}\right)} \right)\:\:\mathrm{rest}\:\mathrm{to}\:\mathrm{simplify}\:\mathrm{A}_{\mathrm{s}} \\$$$$...\mathrm{be}\:\mathrm{continued}... \\$$